2015
DOI: 10.3389/fmicb.2015.01053
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of benthic bacterial diversity in coastal areas contaminated by heavy metals, polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs)

Abstract: Prokaryotes in coastal sediments are fundamental players in the ecosystem functioning and regulate processes relevant in the global biogeochemical cycles. Nevertheless, knowledge on benthic microbial diversity patterns across spatial scales, or as function to anthropogenic influence, is still limited. We investigated the microbial diversity in two of the most chemically polluted sites along the coast of Italy. One site is the Po River Prodelta (Northern Adriatic Sea), which receives contaminant discharge from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
82
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 69 publications
13
82
3
1
Order By: Relevance
“…However, a number of sulfur-oxidizing species such as Sulfuricurvum kujiense, Sulfurimonas autotrophica , and Sulfurovum lithotrophicum , classified within this family, have been isolated from sulfur-rich environments including freshwater nature reserves, hydrothermal vents, and deep-sea sediments58. Helicobacteraceae were also reported as dominant members in coastal sediments contaminated by organic contaminants7. The high AVS concentration and great relative abundances of bacterial groups with potential members relevant with sulfur metabolism suggested that the Yushan area might be suitable for studying the microbial-mediated processes of sulfur metabolism in coastal sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of sulfur-oxidizing species such as Sulfuricurvum kujiense, Sulfurimonas autotrophica , and Sulfurovum lithotrophicum , classified within this family, have been isolated from sulfur-rich environments including freshwater nature reserves, hydrothermal vents, and deep-sea sediments58. Helicobacteraceae were also reported as dominant members in coastal sediments contaminated by organic contaminants7. The high AVS concentration and great relative abundances of bacterial groups with potential members relevant with sulfur metabolism suggested that the Yushan area might be suitable for studying the microbial-mediated processes of sulfur metabolism in coastal sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Benthic prokaryotes play crucial roles in biogeochemical cycling within marine ecosystems123. The diversity of benthic prokaryotes has been investigated across various coastal marine ecosystems456789, demonstrating a wide range of environmental drivers shaping benthic prokaryotic communities such as sediment depth10, water depth11, temperature12, ocean currents5, sediment texture8, salinity6, nutrients13, organic matter quantity and availability14, heavy metals and organic pollutants7. Previous studies have suggested that geographic distance also drives variation in benthic prokaryotic communities1516.…”
mentioning
confidence: 99%
“…The marker size represents the relative abundance of each ASV (scale provided) and bacterial families are represented by different colors. each zone (Martiny et al, 2015;Quero et al, 2015). Microbial signatures are routinely used to identify poor environmental conditions for recreational water use (Fong et al, 2005) and, more recently, studies have shown that microbial markers are also indicators of reef health (Glasl et al, 2017(Glasl et al, , 2019.…”
Section: Potential Microbial Signatures Associated With Sctld Outbreamentioning
confidence: 99%
“…contamination, located along the coast of Italy at the Po River Prodelta (Northern Adriatic Sea) and the Mar Piccolo of Taranto (Ionian Sea)(Quero et al, 2015). There, results revealed that the core microbiome include Clostridia, Cytophagia, Flavobacteria,Archaea (within the classes Methanobacteria and Methanomicrobia) and several classes within the phylum Proteobacteria.…”
mentioning
confidence: 99%